Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

I have seen a previous solution which is not very clear for me. So can someone send me a clearer answer to the attached question 53?

I have seen a previous solution which is not very clear for me. So can someone send me a clearer answer to the attached question 53?

Question Image
Grade:11

1 Answers

Arun
25763 Points
2 years ago
Dear student
Β 
Equation tangent to H at P is xx1-yy1=1
l=(x1+x2+1/x1)/3 and m=y1/3=sqrt(x1^2-1)/3
Β 
now dy/dx(H) at P =dy/dx(S) at P
=>x1/y1 =(x2-x1)/y1
Therefore, l=x1+1/3x1
so, dl/dx1=1- 1/(3x1^2) ,Β 
dm/dx1=1/3
and dm/dx1 =(1/3)*x1/(sqrt(x1^2-3)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free